Sanitation factors and environmentally-based diseases in slum areas of Padang - Putri, Novia Wirna; Ardiningrum, Areta (BKM Public Health and Community Medicine, 2025)
Purpose: This study aimed to analyze the relationship between sanitation factors and the incidence of environmentally based diseases in the slum areas of Padang. Methods: An analytical cross-sectional study was conducted involving 373 households selected through proportional random sampling from 11 sub-districts categorized as slum areas. Data were collected using structured interviews and environmental assessments. Statistical analysis was performed to examine the association between sanitation factors and disease incidence using chi-square tests. Results: Among the total respondents, 74.8% reported experiencing environmentally related diseases. A significant association was found between the source of clean water and disease incidence (p=0.035), with individuals using unprotected water sources being more likely to experience illness. Toilet conditions were also significantly associated (p=0.042), with households having poor toilet facilities exhibiting a higher incidence of disease. Waste management practices and wastewater drainage were associated with disease incidence (p=0.042), suggesting that inadequate disposal methods may contribute to health risks. The presence of mosquito larvae around households was significantly correlated with higher disease rates (p=0.010), indicating the role of vector-borne transmission. Furthermore, healthy home conditions were significantly related to disease incidence (p=0.046), highlighting the importance of proper housing infrastructure in disease prevention. Conclusion: Sanitation factors, including access to clean water, proper toilet facilities, effective waste management, control of mosquito breeding sites, and healthy housing conditions, play a crucial role in reducing environmentally based diseases in slum communities. Public health interventions focusing on improving sanitation infrastructure and promoting hygiene practices are urgently needed.